An efficient Micropropagation Protocol for Nutritionally Rich Varieties of Sweet Potato (Ipomoea batatas L.) - Arathi, Shaji; Hegde, Vivek; N., Sailekshmi; A. V. V., Koundinya (JOURNAL OF ROOT CROPS, 2020)
An efficient and reproducible plant regeneration protocol for nutritionally rich varieties of sweet potato (Ipomoea batatas L.), Gouri and Bhu Sona was developed. The effect of different hormone combinations and types of explants on shoot regeneration was evaluated to optimize the regeneration protocol. Among the explants and hormone combinations tested, only nodal explants with axillary bud of both the varieties produced shoots and the maximum per cent shoot induction in Gouri (100%) was observed in MS medium supplemented with 1.0 mg l-1 BAP and 1.0 mg l-1 BAP along with 1.0 mg l-1 GA3. Similarly, maximum per cent shoot induction (96.67%) in Bhu Sona was observed in the medium supplemented with 0.5 mg l-1 BAP along with 1.0 mg l-1 GA3 and 1.0 mg l-1 BAP. Leaf, petiole and root explants produced compact callus, which did not regenerate into shoots in shoot induction medium. Regenerated shoots were transferred to different rooting media and maximum rooting in both the varieties were observed in MS medium supplemented with 0.5 mg l-1 IBA. An efficient, reproducible plant regeneration protocol developed for sweet potato varieties, Gouri and Bhu Sona can be used for mass production of planting materials of these varieties and/or any other plant biotechnological approaches.